Highly discordant T cell responses in individuals with recent exposure to household tuberculosis. Issue 10 (5th August 2008) - Hesseling, A C; Mandalakas, A M; Kirchner, H L; Chegou, N N; Marais, B J; Stanley, K; Zhu, X; Black, G; Beyers, N; Walzl, G
Abstract : Background: There are limited data comparing interferon-γ release assays (IGRAs) for the detection of Mycobacterium tuberculosis infection in highly endemic settings. Methods: A cross-sectional household contact study was conducted to measure the agreement of two IGRAs in relation to the tuberculin skin test (TST) to detect M tuberculosis infection and to assess the influence of M tuberculosis exposure and age. Results: In 82 individuals in household contact, 93% of children and 42% of adults had a high M tuberculosis contact score. The TST was positive in 78% of adults and 54% of children, the T-SPOT. TB was positive in 89% of children and 66% of adults and the QuantiFERON TB Gold (QTF) was positive in a similar proportion of adults and children (38.1% and 39.6%). In children there was poor agreement between the TST and T-SPOT. TB (κ = −0.15) and the T-SPOT. TB and the QTF (κ = −0.03), but good agreement between the TST and the QTF (κ = 0.78) using 10 mm cut-off. In adults there was fair to moderate agreement between the TST and T-SPOT. TB (κ = 0.38), the TST and QTF (κ = 0.34) and T-SPOT. TB and QTF (κ = −0.50). High levels of exposure to M tuberculosis were associated with at least a sevenfold odds of being T-SPOT. TB positive (95% CI 7.67 to 508.69) and a threefold odds of being QTF positive (95% CI 3.02 to 30.54). There was a significant difference in the magnitude of T-SPOT. TB early secretory antigenic target (ESAT)-6 and culture filtrate protein 10 kD (CFP-10) spot counts between adults and children. Conclusions: The T-SPOT. TB may be more sensitive than the TST or QTF for detecting recent M tuberculosis infection in children. Differences between assays and the predictive utility of these findings for subsequent disease development should be prospectively assessed.